Ensuring Employment in Small Business and Entrepreneurship in the Context of Stabilization of Financial Relations - Nigora Akhralovna Shakirova (International Journal on Economics, Finance and Sustainable Development, 2022)
This article is devoted to one of the most pressing issues of today in the field of employment in small business and entrepreneurship, which studies the need for current employment, the role and place of small business, as well as the impact of small business on employment. The current situation and the opinion of economists have been analyzed and appropriate conclusions and recommendations have been formulated.